Boarding school strategy in Learning Tahfidz Al-Qur'an in Generation 4.0 Era - Huda M, Amril; Rudiamon, Septika; Firman, Firman; Maja, Gergely (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Boarding school was born simultaneously with the birth of the Indonesian nation, which has a vital role in national leadership. Boarding schools are unique and have a maturity that can pass through time, so they have a dual role, namely acting as a spectator in the face of Islam that is polite, peaceful and serene. Boarding school has a uniqueness which is model in education in Indonesia. Boarding school is also an asset owned by the state and even the world today in the 4.0 generation era, especially in learning the tahfidzul Quran. The challenge facing boarding schools in Generation 4.0 is the t learn the tahfidzul Quran, a sophisticated information and communication technology that can cause various life changes. With that, boarding schools can only carelessly use conventional methods such as the reading method, and the strategies used in learning tahfidz al-Qur'an are minimal, with that there needs to be a solution made to improve the techniques used in learning tahfidz al-q -Qur'an -Qur'an in this 4.0 generation era. The results of this study indicate that the strategy used by boarding schools in the learning process of tahfidzul Qur'an in the 4.0 generation era is the strategy used in learning a research learning strategy when choosing the proper and effective method with the right intention to join the tahfiz program.